Gastroesophageal Reflux in Critically Ill Children: A Review. (31st January 2013) - Solana García, Maria José; López-Herce Cid, Jesús; Sánchez Sánchez, César
Abstract : Gastroesophageal reflux (GER) is very common in children due to immaturity of the antireflux barrier. In critically ill patients there is also a high incidence due to a partial or complete loss of pressure of the lower esophageal sphincter though other factors, such as the use of nasogastric tubes, treatment with adrenergic agonists, bronchodilators, or opiates and mechanical ventilation, can further increase the risk of GER. Vomiting and regurgitation are the most common manifestations in infants and are considered pathological when they have repercussions on the nutritional status. In critically ill children, damage to the esophageal mucosa predisposes to digestive tract hemorrhage and nosocomial pneumonia secondary to repeated microaspiration. GER is mainly alkaline in children, as is also the case in critically ill pediatric patients. pH-metry combined with multichannel intraluminal impedance is therefore the technique of choice for diagnosis. The proton pump inhibitors are the drugs of choice for the treatment of GER because they have a greater effect, longer duration of action, and a good safety profile.